Exploring Agriculture :An Introduction to Food and Agriculture, 4th edition/ (Acc: 509 an introduction to food and agriculture - Donahue, Roy Luther, 1908-; Christiansen, James E.; Evans, Everett F. (Englewood Cliffs, N.J. : Prentice-Hall, 1979)
A textbook introducing the basic aspects of agriculture and food production and including information on careers in agriculture, agribusiness, and related fields.
Keywords: Agriculture; Agriculture; Agriculture